Drug consumption of suspected drug-influenced drivers in Hungary (2016–2018). (July 2022) - Institóris, László; Hidvégi, Előd; Kovács, Katalin; Jámbor, Ákos; Dobos, Adrienn; Rárosi, Ferenc; Süvegh, Gábor; Varga, Tibor; Kereszty, Éva M.
Abstract: The hazard caused by driving under the influence of drugs (DUID) is determined by the time of consumption, dose and biological effects of a substance, as well as by synergistic drug interactions after multi-drug use. The aim of this work was to investigate the prevalence and pattern of psychoactive substance use of suspected DUID drivers and to present the advantages and disadvantages of the system currently used for determination of impairment in Hungary. Blood and urine samples, collected between 2016 and 2018, were taken from 2369 drivers with a positivity rate of 95% for at least one substance. Classical illicit drugs were detected in 76–87%, prescription medications in 9–15%, stimulant New Psychoactive Substances (sNPS) in 3–8%, and synthetic cannabinoids (SCs) in 20–22% of the positive samples. The most frequent substances according to substance groups were: classical illicit drugs : cannabis (n = 1240), amphetamine and methamphetamine (AM/MA) (n = 753), MDMA (n = 196), and cocaine (n = 180), medicines : alprazolam (n = 188) and clonazepam (n = 83), sNPS : N-ethyl-hexedrone (n = 115), SCs : 5 F-MDMB-PINACA (n = 267), AMB-FUBINACA (n = 92) and ADB-FUBINACA (n = 90). The median age of classical illicit drugs users was 29 years, prescription medicine users were 33 years old, sNPS users were 28 years, and SC users were 26 years old. Compared to the previous two years, we found pronounced changes in the ratio of sNPS (14% decrease) and SC users (10% increase), and in the pattern of NPS consumption. The ratio of multi-drug use varied between 38% and 50%. 69% of drivers tested positive were deemed impaired. Impairment was determined according to impairment limits (80–82%), multi-drug use (12–13%), and the result of medical investigation when a single active substance with no set impairment limit was detected in the blood (6–8%). The results of medical investigations may be uncertain due to the long time delay between arrest and clinical examination and to the structure of medical investigations created for determination of alcoholic impairment. In conclusion, a revision of the current medical investigation protocol is warranted to standardize clinical symptom scores that better correlate with driving impairment. Highlights: Compared to 2014–15 the ratio of sNPS use decreased, while of SC use increased. The ratio of multi-drug use was 38–50%. 69% of drivers tested positive were classified impaired. Reduction of time delay between arresting and sampling should be necessary. In Hungary the use of SCs did not decrease compared to other European countries.